Majority owner-managers and organizational efficiency - Denis, David J.; Denis, Diane K. (Journal of Corporate Finance, 1994)
By virtue of their ownership position, majority owner-managers appear to be less constrained than managers of firms with more diffuse ownership structures. Despite this, there is no evidence that majority-owned firms perform poorly and there is evidence that majority ownership is surviving as an organizational form. This implies that either these firms substitute other organizational constraints on managerial behavior or that majority control is efficient for some firms. Our analysis uncovers no evidence that majority owner-managers are constrained by other organizational mechanisms. We find that the choice of majority ownership is related to owner-specific rather than firm-specific characteristics. Approximately 80% of the sample majority-owned firms are either characterized by family involvement or are managed by the founder of the firm. Once this family/founder involvement in managing the firm diminishes, the firm is significantly less likely to be majority-controlled.